IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PT. PERTAMINA (PERSERO) PAREPARE - Selvita Sari (Journal AK-99, 2022)
The contribution of sustainable development with corporate sustainability is twofold. First, it helps establish areas that require corporations to focus on: environmental, social, and economic performance. Second, it provides a common social goal for corporations, governments, and civil society to work towards: ecological, social, and economic sustainability. Like sustainable development, corporate social responsibility (CSR) is also broad, as a dialectical concept. This research aims to find out the Implementation of Corporate Social Responsibility (CSR) in PT. Pertamina (Persero) Parepare.Data collection techniques used in this research are interviews, observations, documentation. The data analysis techniques in this study use qualitative descriptive analysis. The results of the study show that the implementation has been carried out by PT. Pertamina (Persero) Parepare is in accordance with the Law governing CSR and the implementation stage is in accordance with the theory put forward by expert opinion. Implementation of CSR program of PT. Pertamina (Persero) Parepare has been implemented well because it is seen from the stage carried out and plus the strategy used and support from the parties involved who make the program run well and smoothly. As well as the success of the CSR program of PT. Pertamina Persero can be seen in the resulting impact, namely by increasing the knowledge of fishermen by cultivating vanamei and tilapia shrimp.